Simultaneous Detection of Multiple DNA Adducts in Human Lung Samples by Isotope-Dilution UPLC-MS/MS - Monien, Bernhard H; Schumacher, Fabian; Herrmann, Kristin; Glatt, Hansruedi; Turesky, Robert J; Chesné, Christophe (Analytical chemistry (Washington), 2015)
Recent studies have demonstrated that various DNA adducts can be detected in human tissues and fluids using liquid chromatography connected to tandem mass spectrometry (LC-MS/MS). However, the utility of a single DNA adduct as a biomarker in risk assessment is debatable because humans are exposed to many genotoxicants. We established a method to measure DNA adducts derived from 16 ubiquitous genotoxicants and developed an analytical technique for their simultaneous quantification by ultra performance liquid chromatography (UPLC)-MS/MS. Methods for the enrichment of the analytes from DNA hydrolysates and chromatographic separation preceding mass spectrometric analysis were optimized, and the resultant technique was used for the simultaneous analysis of the 16 DNA adducts in human lung biopsy specimens. Eleven adducts (formed by benzo[a]pyrene, 1-methylpyrene, 4-aminobiphenyl, 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine, 1-methoxy-3-indolylmethylglucosinolate, 5-hydroxymethylfurfural, and malondialdehyde) were not detected in any tissue sample (limits of detection: 0.02–7.1 adducts/108 nucleosides). 3,N 4-etheno-2′-deoxycytidine and 1,N 6-etheno-2′-deoxyadenosine, formed from 2,3-epoxyaldehydes of endogenous lipid peroxidation products, were present in all subjects (16.9–115.3 and 27.2–179/108 nucleosides, respectively). The same was true for N 2-(trans-methylisoeugenol-3′-yl)-2′-deoxyguanosine, the major adduct of methyleugenol (1.7–23.7/108 nucleosides). A minor adduct of methyleugenol and two adducts of furfuryl alcohol were detected in several pulmonary specimens. Taken together, we developed a targeted approach for the simultaneous mass spectrometric analyses of 16 DNA adducts, which can be easily extended by adducts formed from other mutagens. The method allowed one to detect adducts of furfuryl alcohol and methyleugenol in samples of human lung.